Disentangling the impact of temperature on consumers' attitudes toward nostalgic advertising. (14th May 2022) - Yang, Qiang; Lin, Yanqing; Li, Hongxiu; Huo, Jiale
Abstract: Although the effect of temperature on consumers is ubiquitous, little is known about how temperature affects consumers' attitudes toward nostalgic advertising. Drawing on embodied cognition theory, this study explores the effect of temperature on consumers' attitudes toward nostalgic advertising through the mediator of the affective system. Based on two experiments involving personal and historical nostalgic advertising, our results show that when exposed to comfortable temperature, consumers follow the "assimilative effect" of temperature; warm temperatures trigger more positive attitudes toward nostalgic advertising when compared with cool temperatures. However, when exposed to uncomfortable temperatures, consumers follow the "complementary effect" of temperatures; cold temperatures lead to more positive attitudes toward nostalgic advertising than hot temperatures. Furthermore, the affective system plays a mediating role between temperature and consumers' attitudes toward nostalgic advertising. This study contributes to the literature on temperature in marketing and provides a practical guide for companies to implement nostalgic advertising strategies.